Considerations on methodology used in the World Health Organization 2000 Report Considerações Metodológicas sobre o Relatório 2000 da Organização Mundial de Saúde - Alicia Domingues Ugá; Célia Maria de Almeida; Célia Landmann Szwarcwald; Cláudia Travassos; Francisco Viacava; José Mendes Ribeiro; Nilson do Rosário Costa; Paulo Marchiori Buss; Silvia Porto (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2001)
The article analyzes the World Health Organization Report for 2000, with emphasis placed on the methodology used to analyze the indicators utilized to compare and classify the performance of the health systems of the 191 member countries. The Report's contribution was the compromise of monitoring the performance of the health systems of member countries, but because of the inconsistent way it was elaborated, and the utilization of questionable scientific evaluation methodologies, the Report fails to give a clear picture. A criterion-based methodology revision is imposed. The main problems in evidence are the choice of individual indicators of disparity in health that discount the population profile, the inadequate control of the impact of social disparities over the performance of the systems, the evaluation of the responsibility of systems that are only partially articulated to the right of the citizens, the lack of data for a great number of countries, consequently having inconsistent estimations, and the lack of transparency in the methodological procedures in the calculation of some indicators. The article suggests a wide methodological revision of the Report. O artigo discute o Relatório da Organização Mundial de Saúde para 2000, com ênfase na análise metodológica dos indicadores utilizados para comparar e classificar o desempenho dos sistemas de saúde dos 191 países membros. O Relatório contribui ao colocar na agenda o compromisso de monitorar o desempenho dos sistemas de saúde dos países membros porém, a forma inconsistente de sua elaboração e a utilização de metodologias de avaliação questionáveis cientificamente, impõem uma criteriosa revisão metodológica. Os principais problemas destacados são a escolha de indicadores individuais de desigualdade em saúde que desconsideram o perfil populacional; o controle inadequado do impacto das desigualdades sociais sobre o desempenho dos sistemas; a avaliação da responsabilidade dos sistemas, apenas parcialmente articulada aos direitos dos cidadãos; a ausência de dados para um grande número de países levando a diversas estimativas pouco consistentes; a falta de transparência nos procedimentos metodológicos para o cálculo de alguns dos indicadores. O artigo sugere uma ampla revisão de caráter metodológico do Relatório.